Does moderate weight loss affect subjective health perception in obese individuals? Evidence from field experimental data - Lucas Hafner; Harald Tauchmann; Ansgar Wübker (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
This paper analyzes whether moderate weight reduction improves subjective health perception in obese individuals. To cure possible endogeneity bias in the regression analysis, we use randomized monetary weight loss incentives as instrument for weight change. In contrast to related earlier work that also employed instrumental variables estimation, identification does not rely on long-term, between-individuals weight variation, but on short-term, within-individual weight variation. This allows for identifying short-term effects of moderate reductions in body weight on subjective health. In qualitative terms, our results are in line with previous findings pointing to weight loss in obese individuals resulting in improved subjective health. Yet, in contrast to these, we establish genuine short-term effects. This finding may encourage obese individuals in their weight loss attempts, since they are likely to be immediately rewarded for their efforts by subjective health improvements.
Keywords: I12; C26; C93; 330; self-rated health; BMI; obesity; randomized experiment; short-term effect; instrumental variable